2023
DOI: 10.3390/ma16062466
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behaviour Evaluation of Full Iron Tailings Concrete Columns under Large Eccentric Short-Term Loading

Abstract: In this study, full iron tailings concrete (FITC) was created using iron tailings from a tailings pond in Qian’an, China. Iron tailings account for 86.8% of the total mass of solid raw materials in the FITC. To enable large-scale use of FITC, a comprehensive investigation of the structural behaviour of full-iron tailing-reinforced concrete (FITRC) specimens is warranted. Therefore, eight rectangular reinforced concrete (RC) columns with conventional reinforced concrete (CRC) as a control were tested to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Our research group has reported similar conclusions in related literature. [46][47][48][49] As shown in Figure 9, the development of diagonal cracks in the bending-shear region in the concrete of the FITC beam was closer to the top of the beam than those of the CC beam, indicating that the shear strength of FITC may be lower than that of CC. However, these issues require further study.…”
Section: Crack Distribution and Widthmentioning
confidence: 99%
“…Our research group has reported similar conclusions in related literature. [46][47][48][49] As shown in Figure 9, the development of diagonal cracks in the bending-shear region in the concrete of the FITC beam was closer to the top of the beam than those of the CC beam, indicating that the shear strength of FITC may be lower than that of CC. However, these issues require further study.…”
Section: Crack Distribution and Widthmentioning
confidence: 99%
“…Ma et al [3] studied the structural behavior of full-iron tailing-reinforced concrete (FITRC) columns under high eccentric loading. Six FITRC column and two CRC column specimens were examined to investigate the effects of different raw materials, section dimensions, and eccentricities on the mechanical behavior of RC columns under high eccentric compression.…”
mentioning
confidence: 99%